2019
DOI: 10.21203/rs.2.10648/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

'The mean mummy way' – Experiences of parents instilling eye drops to their young children as described in online forums and blogs

Abstract: Background: Adults often have difficulty instilling eye drops in their own eyes, but little is known about the difficulties experienced by parents when administering eye drops to their young children.The challenges of administering eye drops to children are accentuated by their poor cooperation, but little has been documented about the difficulties experienced by parents when administering eye drops to their young children. This qualitative study explores parents' experiences of administering eye drops to thei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Recent studies found that caregivers of pediatric glaucoma children are experiencing a great caregiving burden due to the required lifelong followup visits and treatments, potential disease progression for their children, loss of wages and bonuses, and children's resistance to medication instillation [35,45,46]. Anxiety, depression, and declined quality of life often follow, which may indirectly infuence the quality of care they provide, including medication adherence [37,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that caregivers of pediatric glaucoma children are experiencing a great caregiving burden due to the required lifelong followup visits and treatments, potential disease progression for their children, loss of wages and bonuses, and children's resistance to medication instillation [35,45,46]. Anxiety, depression, and declined quality of life often follow, which may indirectly infuence the quality of care they provide, including medication adherence [37,45,46].…”
Section: Discussionmentioning
confidence: 99%